2022
DOI: 10.1021/acs.jpcb.2c02755
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Effect of Salts on the Binding of Antimalarial Drug Hydroxychloroquine with Different Sequences of Duplex DNA

Abstract: Hydroxychloroquine (HCQ) is an important antimalarial drug which functions plausibly by targeting the DNA of parasites. Salts play a crucial role in the functionality of various biological processes. Hence, the effect of salts (NaCl and MgCl2) on the binding of HCQ with AT- and CG-DNAs as well as the binding-induced stability of both sequences of DNAs have been investigated using the spectroscopic and molecular dynamics (MD) simulation methods. It has been found that the effect of salts on the binding of HCQ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Phosphate backbone as well as minor and major grooves are three binding sites available in DNA; hence, the binding of any drug molecule with particular sequence may depend on its tendency to accommodate in these binding sites. ,, In order to understand the accommodation of drug molecules in the groove regions of DNA, a DAPI displacement assay has been performed. The fluorescence intensity of DAPI in buffer gets quenched due to the plausible intramolecular proton transfer from the amidino to the indole moiety (black bar in Figure a and black line in Figures S6 and S7).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphate backbone as well as minor and major grooves are three binding sites available in DNA; hence, the binding of any drug molecule with particular sequence may depend on its tendency to accommodate in these binding sites. ,, In order to understand the accommodation of drug molecules in the groove regions of DNA, a DAPI displacement assay has been performed. The fluorescence intensity of DAPI in buffer gets quenched due to the plausible intramolecular proton transfer from the amidino to the indole moiety (black bar in Figure a and black line in Figures S6 and S7).…”
Section: Resultsmentioning
confidence: 99%
“…46 With the addition of the drug, the fluorescence intensity of DAPI decreases further, which suggests that drug molecules intrude into the major groove and enhance the charge transfer process of DAPI. 31,32 It is noticeable that the change in the fluorescence of DAPI on the addition of drug is more prominent for (CG) 6 than C 6 G 6 , which suggests that CLQ/7CLQ interactions with alternate CG nucleobases are important in its higher binding compared to those with continual CG nucleobases. The change in the fluorescence of DAPI is higher in the case of CLQ than 7CLQ, which suggests that the charged group of CLQ intrudes mainly into the major groove of CG DNA, causing the enhanced binding of CLQ.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decrease in the emission intensity of drug molecules is slightly higher for htel than other sequences. Based on the earlier studies, it has been suggested that the fluorescence intensity of antimalarial drugs decreases on binding with DNA. ,, The change in the absorbance and fluorescence data suggest that all the Gq-forming sequences of DNA interact with the drugs; however, the propensity of interaction of htel may be different from that of other sequences.…”
Section: Resultsmentioning
confidence: 99%